PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH (PBL) UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS VIII PADA MATERI SISTEM PENCERNAAN - Hiasintus Luke (SINERGI : Jurnal Riset Ilmiah, 2026)
Classroom learning is expected to foster students’ enthusiasm for learning, thereby increasing their learning intentions and motivation. This condition is closely related to the teaching methods applied by the teacher. Teaching methods have a significant influence because they directly affect students, so teachers must carefully select learning methods that can encourage students to actively engage in learning. One of the common problems in the learning process is low student activeness, which is caused by teacher-centered instruction and limited student involvement in problem-solving activities. To address this issue, a learning model that has the potential to increase student activeness is Problem Based Learning (PBL). This study aimed to improve students’ activeness through the implementation of the Problem Based Learning method in teaching the digestive system material for Grade VIII students at SMPN 1 Kupang Timur. The research employed Classroom Action Research conducted in cycles, consisting of planning, action, observation, and reflection. Data analysis was carried out by calculating the results of observations on teacher activities and student activeness. The results showed a significant increase in student activeness by 30%, from 51% in Cycle I to 81% in Cycle II after improvements in the instructional actions. Teacher activity also increased by 14%, from 75% to 89% in Cycle II. These findings indicate that the implementation of the Problem Based Learning model can effectively improve student activeness in the learning process.